2012
DOI: 10.1021/jf205260g
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Binding of the Flavonoid Diosmetin to Human Serum Albumin by Multispectroscopic Techniques

Abstract: The binding mechanism of molecular interaction between diosmetin and human serum albumin (HSA) in a pH 7.4 phosphate buffer was studied using atomic force microscopy (AFM) and various spectroscopic techniques including fluorescence, resonance light scattering (RLS), UV-vis absorption, circular dichroism (CD), and Fourier transform infrared (FT-IR) spectroscopy. Fluorescence data revealed that the fluorescence quenching of HSA by diosmetin was a static quenching procedure. The binding constants and number of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(97 citation statements)
references
References 44 publications
(65 reference statements)
4
91
2
Order By: Relevance
“…The red shifts of the emission bands for the chalcones suggested that the combinations of drug and protein resulted in the structural changes of the chalcones. 25 These were consistent with the above conclusions that drug-HSA complexes have formed. In addition, 2′,4′,4-triHC, 2′,4′-diHC and 4-HC all showed single fluorescence emission bands along with the fluorescence intensity increasing obviously after interacting with HSA, which may be due to the excited state intramolecular proton transfer (ESPT).…”
Section: Fluorescence Enhancement Of Three Chalcones In the Presence supporting
confidence: 90%
See 1 more Smart Citation
“…The red shifts of the emission bands for the chalcones suggested that the combinations of drug and protein resulted in the structural changes of the chalcones. 25 These were consistent with the above conclusions that drug-HSA complexes have formed. In addition, 2′,4′,4-triHC, 2′,4′-diHC and 4-HC all showed single fluorescence emission bands along with the fluorescence intensity increasing obviously after interacting with HSA, which may be due to the excited state intramolecular proton transfer (ESPT).…”
Section: Fluorescence Enhancement Of Three Chalcones In the Presence supporting
confidence: 90%
“…(1) are listed in These results indicated that the fluorescence quenching process of HSA by three chalcones was mainly a static quenching. 25 Furthermore, these drugs and HSA formed complexes.…”
Section: Fluorescence Quenching Mechanism Of Hsa By Chalconesmentioning
confidence: 99%
“…For dynamic quenching, higher temperatures result in faster diffusion and greater quenching. The quenching constant increases with increasing temperature, but the reverse effect will be observed for static quenching [32]. The results show that the K SV values decrease with increasing temperature, and the values of k q are greater (Table 2), which suggests that the mechanism is static quenching [29].…”
Section: Fluorescence-quenching Mechanismsmentioning
confidence: 85%
“…This phenomenon suggested that kaempferol interacted with the C@O and CAN groups in the protein structure subunits, resulting in the rearrangement of polypeptide carbonyl hydrogen bonding pattern and finally altering the secondary structure of a-glucosidase (Naik, Chimatadar, & Nandibewoor, 2010). To further characterize the secondary structure change of a-glucosidase, the curve-fitted spectra of a-glucosidase infrared amide I bands in the presence and absence of kaempferol were analyzed (Zhang, Wang, & Pan, 2012) The contents of a-helix (1660-1650 cm À1 ), random coil (1648-1638 cm À1 ), b-turn (1680-1660 cm À1 ), b-sheet (1637-1610 cm À1 ) and b-antiparallel (1692-1680 cm À1 ) of free a-glucosidase were 30.6%, 27.5%, 24.1%, 11.6% and 6.2%, respectively (Fig. 2C).…”
Section: Ft-ir Spectra Analysismentioning
confidence: 99%